The hidden girl : a true story of the Holocaust - Kaufman, Lola Rein.; Metzger, Lois. (New York : Scholastic, 2010)
A Jewish girl named Lola is sent into hiding after her mother is killed, but after she is exposed to the Nazis, Lola must flee again, this time into a dirt hole beneath a barn.
Includes bibliographical references.
Accelerated Reader AR
Keywords: Kaufman, Lola Rein -- Juvenile literature; Kaufman, Lola Rein; Jewish children in the Holocaust -- Poland -- Biography -- Juvenile literature; Holocaust survivors -- United States -- Biography -- Juvenile literature; Jewish children in the Holocaust -- Poland; Holocaust survivors